Kinetic and thermodynamic studies on the adsorption of heavy metals from aqueous solution by melanin nanopigment obtained from marine source: Pseudomonas stutzeri. (15th May 2018) - Manirethan, Vishnu; Raval, Keyur; Rajan, Reju; Thaira, Harsha; Balakrishnan, Raj Mohan
Abstract: The difficulty in removal of heavy metals at concentrations below 10 mg/L has led to the exploration of efficient adsorbents for removal of heavy metals. The adsorption capacity of biosynthesized melanin for Mercury (Hg(II)), Chromium (Cr(VI)), Lead (Pb(II)) and Copper (Cu(II)) was investigated at different operating conditions like pH, time, initial concentration and temperature. The heavy metals adsorption process was well illustrated by the Lagergren's pseudo-second-order kinetic model and the equilibrium data fitted excellently to Langmuir isotherm. Maximum adsorption capacity obtained from Langmuir isotherm for Hg(II) was 82.4 mg/g, Cr(VI) was 126.9 mg/g, Pb(II) was 147.5 mg/g and Cu(II) was 167.8 mg/g. The thermodynamic parameters revealed that the adsorption of heavy metals on melanin is favorable, spontaneous and endothermic in nature. Binding of heavy metals on melanin surface was proved by Fourier Transform Infrared Spectroscopy (FT-IR) and X-ray Photoelectron Spectroscopy (XPS). Contemplating the results, biosynthesized melanin can be a potential adsorbent for efficient removal of Hg(II), Cr(VI), Pb(II) and Cu(II) ions from aqueous solution. Graphical abstract: Image 1 Highlights: Melanin nanoparticles were synthesized from marine bacterium Pseudomonas stutzeri. Melanin having numerous functional groups can scavenge heavy metals efficiently. Removal of mercury, chromium, lead and copper at neutral and acidic pH range by chemisorption. Spontaneous, favorable and endothermic adsorption process.